Literature and the Renaissance garden from Elizabeth I to Charles II : England's paradise - Tigner, Amy L. (Literary and scientific cultures of early modernity., 2012)
Spanning the period from Elizabeth I's reign to Charles II's restoration, this study argues the garden is a primary site evincing a progressive narrative of change, a narrative that looks to the Edenic as obtainable ideal in court politics, economic prosperity and national identity in early modern England. The book offers an original take on gardens by including medical and colonial discourse and by considering the perspective of ecocriticism.